2021
DOI: 10.1177/20499361211034065
|View full text |Cite
|
Sign up to set email alerts
|

High expression of neutrophil and monocyte CD64 with simultaneous lack of upregulation of adhesion receptors CD11b, CD162, CD15, CD65 on neutrophils in severe COVID-19

Abstract: Background and Aims: The pronounced neutrophilia observed in patients with coronavirus disease 2019 (COVID-19) infections suggests a role for these leukocytes in the pathology of the disease. Monocyte and neutrophil expression of CD64 and CD11b have been reported as early biomarkers to detect infections. The aim of this study was to study the expression of receptors for IgG (CD64) and adhesion molecules (CD11b, CD15s, CD65, CD162, CD66b) on neutrophils and monocytes in patients with severe COVID-19 after admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…Previous neutrophil degranulation studies using expression of plasma membrane markers showed enhanced azurophilic granule exocytosis, measured by CD63, in COVID-19 ( 28 , 29 , 31 ). Contradictory results were reported for exocytosis of specific (CD66b) and gelatinase (CD11b) granules ( 9 , 28 , 29 , 31 , 32 , 34 , 35 , 46 ). To evaluate degranulation of neutrophil populations from COVID-19 patients, we compared expression of plasma membrane markers of the 4 neutrophil granule subsets, CD35 (secretory vesicles), CD11b (gelatinase granules), CD66b (specific granules), and CD63 (azurophilic granules), among HD NDN, COVID NDN, and COVID LDN before and after stimulation ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous neutrophil degranulation studies using expression of plasma membrane markers showed enhanced azurophilic granule exocytosis, measured by CD63, in COVID-19 ( 28 , 29 , 31 ). Contradictory results were reported for exocytosis of specific (CD66b) and gelatinase (CD11b) granules ( 9 , 28 , 29 , 31 , 32 , 34 , 35 , 46 ). To evaluate degranulation of neutrophil populations from COVID-19 patients, we compared expression of plasma membrane markers of the 4 neutrophil granule subsets, CD35 (secretory vesicles), CD11b (gelatinase granules), CD66b (specific granules), and CD63 (azurophilic granules), among HD NDN, COVID NDN, and COVID LDN before and after stimulation ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies of neutrophil degranulation in COVID-19 described conflicting results, depending on the method of analysis and experimental conditions. Using granule marker expression, exocytosis of specific and gelatinase granules was increased, unchanged, or decreased in severe COVID-19, while azurophilic granules were uniformly mobilized ( 9 , 28 , 29 , 31 , 32 , 36 , 46 ). On the other hand, reports of elevated concentrations of granule cargo in blood and BALF suggest that azurophilic, specific, and gelatinase granules all undergo exocytosis in vivo in COVID-19 ( 21 , 48 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently neutrophil activation patterns have also been explored in COVID-19 [ 12 ]. While CD64 and CD66b were increased, CD11b was not altered on otherwise activated neutrophils, suggesting an immune dysfunction in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…CD11b, CD66b and CD64 are neutrophil activation markers, with low expression in resting neutrophils but excess expression upon proinflammatory stimuli. Most recently, neutrophil activation patterns have also been studied in acute lung injury and acute respiratory distress syndrome related to coronavirus disease 2019 (COVID-19) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Monocyte CD64 expression was also investigated in patients with severe COVID-19. High CD64 expression on monocytes was detected both in children [252] and adults [253] with severe SARS-CoV-2 infection; thus, it seems that this is characteristic feature of severe form of COVID-19.…”
Section: Monocyte Cd64 Expressionmentioning
confidence: 93%